Dolly Parton, gender, and country music - Edwards, Leigh H., 1970- (Indiana University Press, 2018)
Leigh H. Edwards explores Partons roles as musician, actor, author, philanthropist, and entrepreneur to show how her gender subversion highlights the challenges that can be found even in the most seemingly traditional form of American popular music. As Parton depicts herself as simultaneously "real" and "fake," she offers new perspectives on country music's claims of authenticity.